AREAL SPECIFICITY IN SOCIAL DIALECTICISMS - Saidova, S. (Eurasian Journal of Academic Research, 2023)
This article discusses social lexicon, its types, social-household lexicon. The article analyzes of social dialectics and their territorial-areal peculiarities have been carried out. Examples of social dialectics of Sariosia district of Surkhandarya region are given and explained.